2009
DOI: 10.1007/s11107-008-0183-5
|View full text |Cite
|
Sign up to set email alerts
|

An integrated view on monitoring and compensation for dynamic optical networks: from management to physical layer

Abstract: A vertical perspective, ranging from management and routing to physical layer options, concerning dynamic network monitoring and compensation of impairments (M&C), is given. Feasibility, reliability, and performance improvements on reconfigurabl transparent networks are expected to arise from the consolidated assessment of network management and control specifications as a more accurate evaluation of available M&C techniques. In the network layer, physical parameters aware algorithms are foreseen to pursue rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Physical monitoring is proposed by using several techniques. Implementation of OTDR techniques can be used by adapting these techniques to a WDM network, such as the SARDANA network (Teixeira et al 2009). In addition to the problem of physical layer monitoring, several transmission challenges are faced as the network evolves towards a more transparent, passive and extended network.…”
Section: Convergence Between Metro and Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical monitoring is proposed by using several techniques. Implementation of OTDR techniques can be used by adapting these techniques to a WDM network, such as the SARDANA network (Teixeira et al 2009). In addition to the problem of physical layer monitoring, several transmission challenges are faced as the network evolves towards a more transparent, passive and extended network.…”
Section: Convergence Between Metro and Accessmentioning
confidence: 99%
“…Even optical compensation techniques that alleviate the effect of impairments are important to predict the signal quality along a lightpath. Having in mind that, in a wavelength-routed optical network spanning a large geographical area, optical signals may traverse several long fibre segments and a number of different compensation devices, we recognise that an integration view of their effects should be taken into account for selecting a path (Teixeira et al 2009). Impairment-aware routing and wavelength assignment (IA-RWA) algorithms considering TE information together with the locally introduced physical impairments and the availability of compensation devices through the network can be employed to compute a feasible and least-costly (optimal) lightpaths from sources to destinations.…”
Section: Introductionmentioning
confidence: 99%
“…The ITU-T defined, in the recommendation G.697 [1], a list of OPM parameters that might be used for impairment-aware, such as residual chromatic dispersion (CD), total erbium-doped fibre amplifier (EDFA) input and output powers, a channel's optical power budget, optical signal-to-noise ratio (OSNR), and Q-factor as an estimator of the overall optical performance. Considering the need for stable operation it was demonstrated that a reasonable OPM strategy should not rely just on intensive use of different monitoring functions throughout the network [2]. It should, instead, combine margins for uncertainties, estimation (which relies on the database) and monitoring.…”
mentioning
confidence: 99%
“…Together with these applications related to quality monitoring and failure tracking, OPM can also assist the control plane to detect and dynamically set up optical paths taking into account the physical impairments, as commented in the previous Chapter [Tei09]. Therefore, OPM is essential for managing the future optical networks since it includes a wide range of functionalities focused on improving network performances.…”
Section: Optical Performance Monitoringmentioning
confidence: 99%
“…Such requirements are very important from a network operator's perspective because if fulfilled, they enable the operator to deliver guaranteed services to different types of user groups. Hence, it is desirable to include additional functionalities responsible of performance monitoring and fault management inside the intermediate nodes of future optical networks [Tei09]. In this Thesis, the design of the optical network architectures considers the integration between the control plane and management plane so that the network nodes perform new functions, intimately correlated with performance monitoring and recovery schemes.…”
Section: Summary Of the Workmentioning
confidence: 99%